Review Artikel : Pengujian Analisis Metode Kualitatif Terhadap Kandungan Bahan Kimia Obat Pada Jamu Tradisional - Shofia Difa Aulia; Salma Aziz; Selviani Eka Suci; Siti Lulu Lutfiah; Yuliani Dewi; Lia Fikayuniar (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Indonesia is known for its biodiversity of various types, for example, plants, in Indonesia there are around 9000 species of plants that have traditional medicinal properties, 5% as phytopharmaca ingredients, and 1000s of plant species that can be used as herbal medicine. People often manage traditional medicinal herbs with medicinal chemicals so that they are not by the regulations set by the government, this is evidenced by the findings of herbal medicine with medicinal chemicals (BKO).. This review article draws from several national and international research journals released in the period 2012-2022, there are findings of herbal medicine in the Bayuwangi area, Jakarta, Banyumas, Rengel District Market, Pekalongan, Bumiayu, Central Market, Curug District and Probolinggo with herbal findings that have efficacy and chemical content of drugs Glibenclamide (Diabetes Jammu), Sildenafil (Men's Strong Herbal Medicine), Furosemide, Phenolphthalein, Sibutramine (Slimming Herbal Medicine) Dexamethasone, Cyproheftadin (Appetite Enhancement Herb), Theophylline (Shortness of Breathing Herbal Medicine), Paracetamol and Phenylbutason (Jammu) Anti-Pain) was obtained from the Qualitative methods of Thin Layer Chromatography, Spectrophotodesintometry, High Performance Liquid Chromatography, UV-Visible Spectrophotometry, and FTIR